2023
DOI: 10.1186/s12903-023-02756-y
|View full text |Cite
|
Sign up to set email alerts
|

Dental professionals’ perception of their role in the practice of oral health promotion: a qualitative interview study

Abstract: Objective To explore dental professionals’ perceptions of their role in the practice of oral health promotion. Material and method In-depth interviews were conducted with three dentists, one specialist dentist and seven dental hygienists. All were employed in the public dental service in Kalmar County, Sweden and had at least 2 years’ work experience. The interview questions addressed the experience and views of dental professionals with reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…[31] A study done by Dao et al [23] found that most of the participants felt a lack of facilities including equipment to treat these patients. Therefore, similar to other studies , [23][24][25]32] even in the current survey it was presumed that the majority of dentists wished to have or attend additional training in the form of a hands-on workshop or an audio-visual lecture to provide more insights about the PSNAM.…”
Section: Figures 1-10: the Participants Responses To The Questionnair...supporting
confidence: 67%
See 2 more Smart Citations
“…[31] A study done by Dao et al [23] found that most of the participants felt a lack of facilities including equipment to treat these patients. Therefore, similar to other studies , [23][24][25]32] even in the current survey it was presumed that the majority of dentists wished to have or attend additional training in the form of a hands-on workshop or an audio-visual lecture to provide more insights about the PSNAM.…”
Section: Figures 1-10: the Participants Responses To The Questionnair...supporting
confidence: 67%
“…It is also essential that both medical and dental professionals together are responsible for infants with deformities to seek infant oral health care . [25] Both professionals should work together to approximately educate and train themselves to be able to provide comprehensive treatment . [25] Even for the question of knowledge about the design of the PSNAM appliance maximum number of participants were not aware of the appliance design, which was again attributed to the fact that insufficient curriculum was provided for the undergraduate students.…”
Section: Figures 1-10: the Participants Responses To The Questionnair...mentioning
confidence: 99%
See 1 more Smart Citation